Decentralized Electronic Health Record Management with Semantic-Aware Hierarchical Encryption - Kurniyanto, Firdaus Putra; Santoso, Bagus Jati (Indonesian Scientific Journal, 2025)
The rising incidence of cyberattacks targeting electronic health records (EHR) in Indonesia necessitates a robust and context-aware data protection scheme. This paper proposes a decentralised EHR management system that leverages blockchain, IPFS, and a novel Semantic-Aware Hierarchical Encryption (SAHE) algorithm. SAHE enables multi-level access control based on data sensitivity semantics, ensuring privacy while maintaining usability for medical professionals. The system was implemented in a prototype environment and evaluated through stress testing with up to 200 users, achieving an average CPU usage of 55% and a memory consumption of 80.2 MB. Differential cryptanalysis demonstrated a strong avalanche effect ( 50%), with no vulnerabilities found via OWASP ZAP scanning. This architecture offers a promising solution for privacy-preserving, patient-controlled EHR systems, particularly in regions with limited infrastructure.